Global Trade and Food Safety : Winners and Losers in a Fragmented System - Wilson, John S.; Otsuki, Tsunehiro (World Bank, Washington, DC, 2014)
Food safety standards, and the tradeoff between these standards, and agricultural export growth, are at the forefront of the trade policy debate. How food safety is addressed in the world trade system, is critical for developing countries that continue to rely on agricultural exports. In a fragmented system of conflicting national food safety standards, and no globally accepted standards, export prospects for the least developed countries, can be severely limited. The authors examine the impact that adopting international food safety standards, and harmonizing standards would have on global food trade patterns. They estimate the effect of aflatoxin standards in fifteen importing countries (including four developing countries) on exports from thirty one countries (twenty one of them developing). Aflatoxin is a natural substance that can contaminate certain nuts, and grains when storage, and drying facilities are inadequate. The analysis shows that adopting a worldwide standard for aflatoxin B1 (potentially the most toxic of aflatoxins) based on current international guidelines, would increase nut, and cereal trade among the countries studied, by $ 6.1 billion, compared with 1998 levels. This harmonization of standards would increase world exports by $ 38.8 billion.